Knockout of a difficult‐to‐remove CHO host cell protein, lipoprotein lipase, for improved polysorbate stability in monoclonal antibody formulations. Issue 5 (27th December 2016) - Chiu, Josephine; Valente, Kristin N.; Levy, Nicholas E.; Min, Lie; Lenhoff, Abraham M.; Lee, Kelvin H.
ABSTRACT: While the majority of host cell protein (HCP) impurities are effectively removed in typical downstream purification processes, a small population of HCPs are particularly challenging. Previous studies have identified HCPs that are challenging for a variety of reasons. Lipoprotein lipase (LPL)—a Chinese hamster ovary (CHO) HCP that functions to hydrolyze esters in triglycerides—was one of ten HCPs identified in previous studies as being susceptible to retention in downstream processing. LPL may degrade polysorbate 80 (PS‐80) and polysorbate 20 (PS‐20) in final product formulations due to the structural similarity between polysorbates and triglycerides. In this work, recombinant LPL was found to have enzymatic activity against PS‐80 and PS‐20 in a range of solution conditions that are typical of mAb formulations. LPL knockout CHO cells were created with CRISPR and TALEN technologies and resulting cell culture harvest fluid demonstrated significantly reduced polysorbate degradation without significant impact on cell viability when compared to wild‐type samples. Biotechnol. Bioeng. 2017;114: 1006–1015. © 2016 Wiley Periodicals, Inc. Abstract : CHO lipoprotein lipase (LPL) is one of a number of difficult to remove host cell proteins. CHO LPL that is not cleared from drug product may be able to enzymatically degrade polysorbates. A gene knockout study, as well as an LPL inhibitor study, demonstrated reduced levels of polysorbate degradation.